Reinventando la comunicación interna en un contexto de transformación del negocio: caso Belcorp - Cervera Sevil, María Luisa (2020)
This project describes the design and implementation of the strategic communication plan for Belcorp, as part of the reorganization of the company´s business’ strategy inth e beginning of 2018. The main objective was to support the new strategic priorities and growth goals in sales and profit set for 2021, throughout the 14 countries where Belcorp operates. The strategic communication plan helped Belcorp to align employees with the business’ strategy of the company, including them in the process of transformation. Ultimately, it demonstrated the importance and strategic role of communication in the management of the company. This project serves as a reference for companies such as Belcorp, as well as the leaders and communication professionals within them, who are currently or about to embark in significant restructuring processes in an environment marked by technology, and who seek to leverage communication as a strategic element in generating credibility and participation from employees.